2019
DOI: 10.1002/asjc.1999
|View full text |Cite
|
Sign up to set email alerts
|

Robust PID controller for flexible satellite attitude control under angular velocity and control torque constraint

Abstract: A PID controller for flexible satellite attitude control with unknown perturbation is proposed in this paper. System inertia uncertainty, stochastic disturbance torque, and perturbation of flexible deformation are discussed, and the controller proposed in this paper is robust to these perturbations. A novel integral term is designed; hence the Lyapunov function structure is modified and the stability proof is simplified. The angular velocity constraint is discussed and a novel method to solve the angular veloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
0
8
0
1
Order By: Relevance
“…Property (1) is fairly obvious, which can be obtained from the definition of the gain factor ρ i . In fact, the function of ρ i is to reduce the PID terms proportionally when control torque saturation occurs, and based on the conclusion in [18], this method does not change system stability. When saturation occurs, the PID terms are reduced to a relatively small value, and based on the definition of ρ i , it could be found that, in this condition, the control output is locked to the system norm upper bound, and this is how the control saturation issue is solved in this paper.…”
Section: Controller Performance Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Property (1) is fairly obvious, which can be obtained from the definition of the gain factor ρ i . In fact, the function of ρ i is to reduce the PID terms proportionally when control torque saturation occurs, and based on the conclusion in [18], this method does not change system stability. When saturation occurs, the PID terms are reduced to a relatively small value, and based on the definition of ρ i , it could be found that, in this condition, the control output is locked to the system norm upper bound, and this is how the control saturation issue is solved in this paper.…”
Section: Controller Performance Analysismentioning
confidence: 99%
“…Su et al [14] designed a nonlinear PD controller for the attitude control of the helicopter. Li et al [15][16][17][18] also had done some work focusing on PID and sliding mode controller design. In their work, the main focus is the modification of standard PID and sliding mode controllers.…”
Section: Introductionmentioning
confidence: 99%
“…However, designing a high‐precision and reliable attitude controller is quite difficult due to the existence of external disturbances involving gravitational torque, aerodynamic torque and radiation torque, inertial uncertainties arising from fuel consumption, payload variation and appendage deployment, actuator failures with partial or total loss of efficiency, and input saturation constraints. Over the past decades, extensive efforts have been devoted to the spacecraft ATC and numerous control schemes are now available in the literature, such as inverse optimal control [1],[2], variable structure control [3‐5], PID control [6,7], H ∞ control [8,9], optimal output feedback control [10], and exponential and resilient control [11]. With the development of universal approximation techniques, fuzzy logic system (FLS) [12] and neural network (NN) [13] are widely used to estimate the unknown nonlinear functions in spacecraft dynamics [14‐16].…”
Section: Introductionmentioning
confidence: 99%
“…Proportional–integral–derivative (PID) control technique is designed to control the voltage of islanded MG . Simple design, ease of implementation and low order transfer function matrices are the motivations for this controller.…”
Section: Introductionmentioning
confidence: 99%